On Tetragonicipitidae (Crustacea, Copepoda) from the Channel of São Sebastião, Brazil, with description of their nauplii and two new species of Phyllopodopsyllus - Björnberg, Tagea; Kihara, Terue C. (Zootaxa, 2013)
Phyllopodopsyllus iuanamai sp. nov. and Phyllopodopsyllus pseudokunzi sp. nov. are described from specimens collected in the Channel of São Sebastião (State of São Paulo, Brazil). The nauplii of P. iuanamai, P. pseudokunzi, P. aegypticus Nicholls, 1944 are described, additional information is given on nauplii and morphology of the adult P. setouchiensis Kitazima, 1981, and on the nauplius of Laophontella horrida (Por, 1964). These represent first records of P. aegypticus and L. horrida in Brazilian waters.